Islamic Law Guidelines Regarding The Banjar People's Belief In Using Turmeric And Whiting To Cure "Kepidaraan" - Lestari, Bunga; Hafidzi, Anwar; Layli Nor Syifa; Muhammad Ilham Nadhir; Irwanda Fikri; Hayatun Na`Imah; Dr. H. Hamdan Mahmud, M.Ag (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
ABSTRACT This research examines the beliefs of the Banjar people in carrying out bapidara, namely the culture of overcoming fever which is believed to be caused by disturbances from spirits, also called kepidaraan. Treatment is done using natural ingredients such as turmeric and whiting. Bapidara has been a tradition for generations of the Banjar people and not just anyone can do it. Fever can be cured by applying a concoction of turmeric and whiting accompanied by reciting several mantras. The method used in this study is a qualitative descriptive analysis method, namely analyzing data obtained from interviews and field observations. From the results of this study, it can be concluded that this bapidara treatment does not deviate from Islamic law, basically turmeric and betel lime have their own benefits that can treat fever and also the readings used are certain verses contained in the Koran. Suggestions and beliefs also affect conditions, regarding the disturbance of these spirits, they return to their respective beliefs. Keywords: Bapidara, Banjar, Turmeric and Whiting.   ABSTRAK Penelitian ini mengkaji mengenai kepercayaan masyarakat Banjar dalam melakukan bapidara yaitu budaya mengatasi demam yang dipercaya karena gangguan makhluk halus, disebut juga dengan kepidaraan. Pengobatan dilakukan dengan menggunakan bahan alami seperti kunyit dan kapur sirih. Bapidara sudah menjadi tradisi turun temurun masyarakat Banjar dan tidak sembarang orang dapat melakukannya, demam dapat sembuh dengan mengoleskan ramuan kunyit dan kapur sirih disertai dengan membaca beberapa mantra. Metode yang digunakan dalam penelitian ini adalah metode analisis deskriptif kualitatif, yaitu menganalis data yang diperoleh dari hasil wawancara dan pengamatan lapangan. Dari hasil penelitian ini dapat disimpulkan bahwa pengobatan bapidara ini tidak menyimpang dari hukum islam, pada dasarnya kunyit dan kapur sirih memiliki manfaat tersendiri yang bisa mengobati demam dan juga bacaan yang digunakan adalah ayat-ayat tertentu yang terdapat didalam al-quran. Sugesti dan keyakinan juga mempengaruhi kondisi, mengenai gangguan makhluk halus ini kembali lagi pada kepercayaan masing-masing. Kata kunci: Bapidara, Banjar, Kunyit dan Kapur Sirih.